Design and management of cloud assisted smart ICU for Covid-19 patients real-time health parameters measurement based on IoT's through wireless sensor network - G.M. Sharif Ullah Al-Mamun; Firuz Kabir (Northern Negros State College of Science and Technology (NONESCOST), 2021)
A smart healthcare monitoring and measurement system are designed to use in hospitals for monitoring various parameters such as oxygen level, ECG, temperature, humidity, blood pressure for Covid-19 patient, who needs an ICU. This framework can be carried out for numerous biological applications. Network of Covid-19 patient's nodes must be available in the ICU room for measurement. A base node collects all these signals and this is to be monitored in the monitoring room which is connected to the Cloud system for real-time monetization from any time anywhere. An ESP32 board is used in all nodes. For transferring ECG signals and other health parameters to the remote doctor, a smart ICU patient health monitor framework utilizing ESP-32 Web Server is deployed. Thus, the remote specialist doctor could be checking his patients' condition through the web. In this project, AD8232 ECG Sensor is interfaced with ESP32 Module and observe the ECG signal on Ubidots platform. The other sensors that connected with the module show the current state of the ICU Covid patient. Through this doctors and other medical staff can easily remotely monitor the patient in real-time.